A Self-Assessment Tool for Helping Identify Police Burnout Among Investigators of Child Sexual Abuse Material - Kimberly J. Mitchell, PhD; Jennifer E. O'Brien, PhD; Ateret Gewirtz-Meydan, PhD (Elsevier, 2024)
Introduction: Law enforcement professionals who investigate crimes involving child sexual abuse material face increased risk of mental health challenges, including burnout. This study aims to develop a data-driven self-assessment tool for law enforcement personnel exposed to child sexual abuse material. The tool assesses burnout symptoms and related mental health issues, offering a proactive approach to identifying and supporting individuals at risk. Methods: A mixed-methods investigation involved 500 police investigators and forensic examiners across the U.S. The study utilized a convenience sample recruited through various channels connected with the National Criminal Justice Training Center. Results: Twenty percent of participants exhibited high burnout. The Burnout Self-Assessment Tool demonstrated a sensitivity of 69.6% and specificity of 74.6% at a cut-off point ≥2, correctly classifying 73.6% of the sample. Individuals with scores ≥2 were 3.47 times more likely to be experiencing high burnout than peers with a score of zero, with increasing odds with each additional score. High burnout was associated with longer tenure in current positions. Conclusions: The Burnout Self-Assessment Tool offers a short and simple self-assessment tool for law enforcement professionals exposed to child sexual abuse material, aiding in the early identification of burnout symptoms. A cut-off point ≥2 provides a data-driven strategy for identifying individuals at increased risk, promoting timely intervention and support to mitigate burnout's adverse effects on mental well-being and professional performance. The Burnout Self-Assessment Tool's sensitivity and specificity balance enhances its utility, providing a proactive approach to address the unique mental health challenges faced by law enforcement personnel combating crimes involving child sexual abuse material.